Incremental forming of tubes and sheets assisted by friction-induced heating - Homberg, Werner; Hornjak, Daniel; Beerwald, Charlotte; Rostek, Tim; Kunert, Joachim; Wilk, D.

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Key Engineering Materials)
This article will highlight various aspects of the production process of high performance active elements made of ultra high-strength steels. Focus is put on the processing of thick sheet metal regarding hot forming by means of punching, embossing, and forging processes as well as on thermo-mechanical treatment. Due to the material thickness of the semi-finished parts/blanks used and owing to the high strength of the materials (Rm > 2600 MPa) current production techniques and parameters from the field of thin sheet metal can only be limitedly be transferred and have therefore been specially investigated for this application.

Presshärten von Rohren und Profilen mittels formlos fester Stoffe - Mennecart, Thomas; Rostek, Tim; Witulski, Jörg; Brosius, Alexander; Takkaya, A. Erman; Homberg, Werner

High Performance Active Elements for Agricultural Machines Made of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Proceedings. of the 10th International Conference on Technology of Plasticity (ICTP))

Presshärten von Rohren und Profilen mittels formlos festen Stoffen - Tekkaya, A. Erman; Mennecart, Thomas; Witulski, Jörg; Homberg, Werner; Rostek, Tim

Grundlegende Untersuchung der Prozess- und Werkzeugparameter und ihrer Wechselwirkungen für das thermo-mechanisch unterstützte inkrementelle Umformverfahren des Reib-Drückens - Hornjak, Daniel

Hochleistungsaktivelemente für landwirtschaftliche Maschinen aus ultrahochfestem Stahl - Homberg, Werner; Rostek, Tim

Thermo-Mechanical Hardening of Ultra High-Strength Steels - Homberg, Werner; Rostek, Tim (Key Engineering Materials)
nnovative ultra high-strength steels have excellent mechanical properties which commonly relate to the materials martensitic microstructure. As thermal heat treatments are state-of-the-art for obtaining the desired microstructure, innovative thermo-mechanical treatments are likely to give rise to even better material qualities. This article highlights various aspects of innovative thermo-mechanical hardening strategies for the processing of ultra high-strength steels, involving both press hardening and friction spinning operations.

Processing of Ultra High-Strength Steels involving Thermo-mechanical Hardening Effects - Homberg, Werner; Rostek, Tim

Ein Beitrag zur Verarbeitung von Dickblech aus utlrahochfesten Stahlwerkstoffen - Rostek, Tim
Die Fertigung von innovativen Bauteilen aus ultrahochfesten Stählen erfordert oft Wärmebehandlungen zur Einstellung höchster mechanischer Festigkeiten. Bei Einsatz dickwandiger Halbzeuge mit entsprechend hoher Wärmekapazität eignen sich konventionelle Wärmebehandlungstechnologien und -prozessführungen jedoch nur eingeschränkt für einen effizienten Herstellungsprozess. Inhalt dieser Arbeit sind daher innovative Fertigungsstrategien, welche die wirtschaftliche Herstellung entsprechender Bauteile vor dem Hintergrund einer effektiven Formgebung sowie einer anforderungsangepassten Werkstoffbehandlung zum Ziel haben. Spezielle Temperaturführungsstrategien als auch thermomechanische Herangehensweisen zum Einstellen besonders günstiger mechanischer Eigenschaften entsprechender Stahlwerkstoffe stellen in diesem Kontext vielversprechende Ansatzpunkte dar.

Innovative Processing Techniques for the Manufacture of High-Performance Active Elements from Ultra High-Strength Steel Plate - Homberg, Werner; Rostek, Tim

Internal Flow-Turning - An Innovative Technology for the Manufacture of Tailored Tubes - Homberg, Werner; Rostek, Tim; Wiens, Eugen (Key Engineering Materials)
In order to optimise the material utilisation and improve the lightweight design of automotive parts tailored hollow profiles are needed, especially as semi-finished parts for hydroforming. Internal Flow-Turning is an innovative incremental forming technology which enables the manufacture of tubes featuring a varying wall thickness and a constant outer diameter. These characteristics facilitate the material feed at hydroforming processes significantly. In addition, the spinning-related forming technology improves the mechanical material properties, shape and dimensional accuracy, and the surface quality of parts produced.

Layered Steel Materials for the Manufacture of Self-Sharpening Cutting Blades - Rostek, Tim; Homberg, Werner (International Journal of Material Forming)

Friction-Spinning – Possibility of Grain Structure Adjustment - Lossen, Benjamin; Andreiev, Anatolii; Homberg, Werner; Schaper, Mirko (Procedia Engineering)

Rubber pad forming - Efficient approach for the manufacturing of complex structured sheet metal blanks for food industry - Spoelstra, Paul; Djakow, Eugen; Homberg, Werner

Incremental electrohydraulic forming - A new approach for the manufacture of structured multifunctional sheet metal blanks - Djakow, Eugen; Springer, Robert; Homberg, Werner; Piper, Mark; Tran, Julian; Zibart, Alexander; Kenig, Eugeny

Locally Graded Steel Materials for Self-Sharpening Cutting Blades - Rostek, Tim; Homberg, Werner (Procedia Engineering)

Development of hybrid directionally reinforced structural parts for lightweight applications - Homberg, Werner; Rostek, Tim; Schaper, Mirko; Grydin, Olexandr; Andreiev, Anatolii; Brosius, Alexander; Tulke, Marc

Locally Graded Steel Materials for Self-Sharpening Cutting Blades - Rostek, Tim; Homberg, Werner

Internal Flow-Turning – a new approach for the manufacture of tailored tubes with a constant external diameter - Wiens, Eugen; Homberg, Werner (Procedia Engineering)
Keywords: Applied Mathematics

Internal flow-turning – efficient manufacture of load-adapted tubes with a constant external diameter - Wiens, Eugen; Homberg, Werner (Proceedings of the International Conference on Steels in Cars and Trucks SCT 2017)

Walzen statt drehen - Wiens, Eugen (Bänder Bleche Rohre)

Optimization of Tooling Design for Hot Mandrel Bending of Pipe Elbows - Diekmann, Uwe; Homberg, Werner; Prehm, Jens; Rostek, Tim; Schönhoff, Nils; Tabakajew, Dmitri; Trasca, Andreea; Uysal, Haris (Materials Science Forum)
This paper presents the finite element model developed for the simulation of pipe elbow production by the so-called ‘Hamburg process’ in order to improve productivity and resource efficiency. To optimize the tooling design, a sensitivity analysis of the tool parameters that influence the quality of pipe elbows, such as mandrel height and length, is conducted. Different materials data sets including damage models were considered. Using numerical simulations, it is possible to determine an optimized tool geometry for the production of specific pipe elbow dimensions. Furthermore, as a result of the experiments and numerical simulations conducted, it is possible to increase the production velocity of the serial plant. Along with deformation, damage models are included in simulations in order to identify the right process boundaries. Finally, an experimentally validated model is developed for increasing resource efficiency in pipe elbow fabrication.

Grading Technologies for the Tanufacture of Innovative Cutting Blades - Rostek, Tim; Homberg, Werner (AIP Conference Proceedings 1960, 100013)

Hybride Verbundstrukturen aus Aluminium und Titan für Leichtbauanwendungen - Homberg, Werner; Rostek, Tim; Schaper, Mirko; Grydin, Olexandr; Andreiev, Anatolii; Brosius, Alexander; Guilleaume, Christina

Herstellung innovativer Stahlhalbzeuge mit wanddicke- und festigkeitsveränderlichen Eigenschaften für den Leichtbau durch Innendrückwalzen (IDW) - Wiens, Eugen; Homberg, Werner

Internal Flow-Turning – extended manufacturing possibilities in tailored tube production - Wiens, Eugen; Homberg, Werner (MATEC Web of Conferences)

LHYBS – Lightweight Design by Novel Hybrid Materials - Camberg, Alan Adam; Tröster, Thomas; Heggemann, Thomas; Homberg, H.; Schaper, Mirko; Dietrich, J.; Bremser, Wolfgang; Achterberg, L.; Kabst, M.; Wille, M.; Peckhaus, Volker

Friction-spinning—Grain structure modification and the impact on stress/strain behaviour - Lossen, Benjamin; Andreiev, Anatolii; Stolbchenko, Mykhailo; Homberg, Werner; Schaper, Mirko (Journal of Materials Processing Technology)

Deep drawing of fiber metal laminates for automotive lightweight structures - Heggemann, Thomas; Homberg, Werner (Composite Structures)
Current challenges in the automotive industry are the reduction of fuel consumption and the CO2 emissions of future car generations. These aims can be achieved by reducing the weight of the car, which further improves the driving dynamics. In most currently mass-produced cars, the body accounts for one of the largest parts by weight, and hence designing a lightweight car body assumes great importance for reducing fuel consumption and CO2 emissions. Extremely lightweight designs can be achieved by using purely composite materials, which are very light but also highly cost intensive and not yet suitable for large scale production due to the necessity of manual processing. A promising approach for the automated, large-scale production of lightweight car structures with a high stiffness to weight ratio is the combination of high strength steel alloys and CFRP prepregs in a special hybrid material/fiber metal laminate (FML) – which can be further processed by forming technologies such as deep drawing. In current research work at the Chair of Forming and Machining Technology (LUF) at the University of Paderborn, innovative manufacturing processes are being developed for the production of high strength automotive structural components made of fiber metal laminates. This paper presents the results of technological and numerical research that is currently being performed at the LUF into the forming of hybrid fiber metal laminates. This paper focuses on the results of basic research and the individual measures (tool, process and material design) necessary for achieving the desired part quality.

Intrinsically lubricated tool inserts for deep drawing applications generated by selective laser melting - Bader, Fabian; Hengsbach, Florian; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)
Abstract. Within the scope of this study, an intrinsically lubricated deep drawing die fabricated via laser beam melting (LBM) is investigated. In contrast to the common objective of generating highly dense LBM components, this work endeavors to achieve intended micro-scale porosity. By utilizing permeable structures, in-process closed-loop control of lubrication during the forming operations is feasible. Based on a modified AM scan strategy, the required filigree, porous structures can be generated. Thus, in the present work three permeable specimens are additively generated from the maraging steel 1.2709. The cylindrical specimens are then analyzed via light microscopy (LM), microcomputer tomography (microCT), and with regard to the oil throughput rate. Subsequently, an intrinsically lubricated, AM deep drawing tool die is manufactured and experimentally tested. The findings reveal interesting results for deep drawn specimens with AM deep drawing dies.

Al2O3/ZrO2-8Y2O3 and (Cr,Ti)AlSiN tool coatings to influence the temperature and surface quality in friction-spinning processes - Tillmann, Wolfgang; Fehr, Alexander; Stangier, Dominic; Dildrop, Markus; Homberg, Werner; Lossen, Benjamin; Hijazi, Dina (Production Engineering)
Friction-spinning is an incremental forming process, which is accompanied by complex thermal and mechanical loads in the tool and the formed part. To influence the process temperature, two main process parameters, i.e. the rotation speed and the feed rate, can be adapted. With the objective to improve the tool performance and the quality of the workpiece, this study focuses on a coating concept for friction-spinning tools made of high speed steel (HS6 5 2C, 1.3343). On the one hand, atmospheric plasma sprayed (APS) Al2O3 and ZrO2-8Y2O3 coatings serve as a thermal insulator, and, on the other hand, physically vapor deposited (PVD) TiAlSi7.9N and CrAlSi7.5N films are applied to increase the hardness and wear resistance of the tools. In addition, duplex coatings, combining the APS and PVD technique, are synthesized to influence both the heat transfer and the tribological properties of friction-spinning tools. Subsequently, all coated tools are tested in a friction-spinning process to form flanges made of AW-6060 (AlMgSi 3.3206) tube materials. The tool temperatures are determined in-situ to investigate the impact of the tool coating on the process temperature. Compared to an uncoated tool, the alumina and zirconia coatings contribute to a reduction of the tool temperature by up to half, while the PVD films increase the hardness of the tool by 20 GPa. Furthermore, it is shown that the surface quality of thermally sprayed (TS) or PVD coated tools is directly related to the surface roughness of the resulting workpiece.

Ein Beitrag zur kombinierten (quasi-)statischen und dynamischen Umformung von blechförmigen Halbzeugen - Djakow, Eugen
Working-media-based forming processes (WMBF) represent a great potential regarding the production of complex sheet-metal lightweight components with excellent surface quality, shape accuracy and dimensional stability. The working-media-based forming processes characterize the sheet-metal forming process, where the sheet metal blank is formed during the forming process by means of a (quasi-)static or dynamic working media pressure into a contouring forming tool. Although the WMBF offers improved utilization of the formability of the used materials compared to conventional sheet metal forming processes, there are limits in the production of complex deeper or sharp edged components with (quasi-)static and dynamic WMBF processes, which can not be overcome by using these methods alone. In order to overcome this, multi-level WMBF process sequences for components with spherical and stepped geometries are developed in this work. Here the developed strategies combine the advantages of (quasi-)static and dynamic WMBF processes. Furthermore, based on analytical, experimental and numerical investigations, innovative process management strategies were derived, which completely compensate the local wall thickness changes, make better use of existing material resources and thus enable the safe production of mentioned geometries.
Keywords: High Speed Forming

High-Speed Incremental Forming – New Technologies For Flexible Production Of Sheet Metal Parts - Linnemann, M.; Psyk, V.; Djakow, Eugen; Springer, R.; Homberg, W.; Landgrebe, D. (Procedia Manufacturing)

Heat transfer enhancement in pillow-plate heat exchangers with dimpled surfaces: A numerical study - Piper, M.; Zibart, A.; Djakow, Eugen; Springer, R.; Homberg, W.; Kenig, E.Y. (Applied Thermal Engineering)

Ein Beitrag zur kombinierten (quasi-)statischen und dynamischen Umformung von blechförmigen Halbzeugen - Djakow, Eugen

Simulationsgestützte Analyse und Optimierung der Umformung geschlossener Stahlprofile mittels Hamburger Verfahren - Tabakajew, Dmitri

Ein Beitrag zum stoffschlüssigen Fügen durch plastische Deformation: partielles Kaltpressschweißen durch inkrementelles Walzen - Schmidt, Hans Christian

Ein Beitrag zur Herstellung von hybriden Bauteilen mittels Reibdrücken - Lossen, Benjamin

Improved set up strategies for steel strip straightening machines - Rostek, Tim; Homberg, Werner (AIP Conference Proceedings 2113, 170018)

Forming analysis of tailored tubes with an internal contoured wall thickness and external axial ribs manufactured by internal flow-turning - Wiens, Eugen; Homberg, Werner (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)

Combined Curing and Forming of Fiber Metal Laminates - Heggemann, Thomas; Homberg, Werner; Sapli, Hüseyin (Procedia Manufacturing)

Combined Curing and Deep Drawing of Fiber Metal Laminates to Spherical Hybrid Components - Sapli, Hüseyin; Heggemann, Thomas; Homberg, Werner

Microstructural investigation on phase transformation during flow forming of the metastable austenite AISI 304 - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (54. Metallographie-Tagung)

Joining with Versatile Friction-Spun Joint Connectors - Rostek, Tim; Wiens, Eugen; Homberg, Werner (Procedia Manufacturing)

Some ideas for the further development of hydroforming process chains - Wiens, Eugen; Djakow, Eugen; Homberg, Werner (Nebu/Nehy 2020)
Even though the spectrum of parts is expected to shift over the long term as a result of increasing e-mobility, there is still an extremely high demand for complex components made of high-strength materials which can only be produced by hydroforming technologies. The innovative combination of hydroforming processes with other forming processes, as well as the improvement of the processes themselves, offers considerable potential for improvement. A number of promising ways of improving the hydroforming process chain are therefore the subject of this contribution. The focus of the article is on possible approaches for combining (incremental) pre- and post-forming operations, which can permit considerable improvements in both quality and features at a reduced cost. Furthermore, a novel combination of quasi-static and high-speed forming processes is presented, leading to an improved overall forming process (with a high application potential) for the production of complex parts.
Keywords: Hydroforming; Incremental Forming; Internal Flow-turning; High-speed Forming

Experimental and Numerical Investigations into the Influence of the Process Parameters During the Deep Drawing of Fiber Metal Laminates - Heggemann, Thomas; Sapli, Hüseyin; Homberg, W. (Forming the Future)

Improving the Accuracy of Deep Drawn Fiber-Metal Laminate Parts by Preliminary Surface Treatment - Voswinkel, Dietrich; Sapli, Hüseyin; Kloidt, Dennis; Heggemann, Thomas; Homberg, Werner; Grydin, Olexandr; Schaper, Mirko (IOP Conference Series: Materials Science and Engineering)

Innovative Measurement Of Stress Superposed Steel Strip For Straightening Machines - Bader, Fabian; Bathelt, Lukas; Djakow, Eugen; Homberg, Werner; Henke, Christian; Trächtler, Ansgar (ESAFORM 2021)
Higher quality requirements by customers demand higher precision and accuracy from manufacturing processes. Application oriented preparation of semi-finished materials is key for subsequent forming operations, therefore, straightening machines are employed. Straightening strengthens the material by increasing plastic deformation by means of strain hardening, resulting in undesirable reduction in formability when processing high strength materials, in particular. Conventional roll-type straightening machines process either bars or strips. This is achieved upon passing material between rolls arranged in two staggered rows. However, conventional straightening processes do not adapt to the local varying distortion of coiled strips. Innovative, self-correcting process control techniques, which adapt to the initial geometric characteristics of the strip, present a promising approach to fix this issue through optimization of the leveling process. Here, an innovative strategy to improve straightening of high strength steel materials (1.4310) is presented. This implements optimized leveling, adding minimal plastic deformation and, thus, strain hardening. To operate an intelligent straightening machine, a reliable online measurement of the surface defects is fundamentally essential. The MagnaTest, which is developed for material testing, is made feasible for such purposes after calibrating for curvature measurement. Preliminary results are promising in regards to measuring the curvature online, so that the following straightening process can be close loop controlled. The bending measurement is linked to open/closed loop control, therefore providing an optimal straightening result in regards to formability, leveling, and reduced strain hardening.

Self-optimized, Intelligent Open-Loop-Controlled Steel Strip Straightening Machine for Advanced Formability - Bader, Fabian; Bathelt, Lukas; Djakow, Eugen; Homberg, Werner; Henke, Christian; Trächtler, Ansgar (Forming the Future)
Innovative self-correcting process control techniques which adapt to the initial geometric characteristics of the strip are a promising approach to fix the local varying distortion of coiled strips by optimizing the leveling process. This paper presents an innovative strategy to improve straightening of AHSS materials (1.4310). This implies optimized leveling, adding minimal plastic deformation, and, thus, strain hardening. Therefore, an “intelligent straightening machine” is being developed which will be presented. To operate an intelligent straightening machine a reliable online measurement of the surface defects is fundamentally essential. This paper describes an approach towards the measurement of a bent steel strip for an automatic straightening process. Therefore, various ways of measuring the bending curvature are investigated. Optical, tactile, and the electromagnetic induction testing MagnaTest are compared with each other. The bending measurement is linked to open-loop control, providing an optimal straightening result in regards of formability, leveling, and reduced strain hardening.